2008
DOI: 10.7326/0003-4819-149-8-200810210-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Nurse-Led Disease Management for Heart Failure in an Ethnically Diverse Urban Community

Abstract: Background Randomized, controlled trials have shown that nurse-led disease management for patients with heart failure can reduce hospitalizations. Less is known about the cost-effectiveness of these interventions. Objective To estimate the cost-effectiveness of a nurse-led disease management intervention over 12 months, implemented in a randomized, controlled effectiveness trial. Design Cost-effectiveness analysis conducted alongside a randomized trial. Data Sources Medical costs from administrative reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 22 publications
(25 reference statements)
1
99
0
3
Order By: Relevance
“…Direct healthcare costs, such as costs of hospitalization, emergency room (ER) visits, medication and healthcare staff were always included in the economic evaluations. Three studies also included direct non-healthcare costs such as travel costs to the healthcare facility [34,45,46]. Three studies additionally incorporated indirect non-healthcare costs such as productivity loss, lost wages, and income lost by family caregivers [36,47,48].…”
Section: Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Direct healthcare costs, such as costs of hospitalization, emergency room (ER) visits, medication and healthcare staff were always included in the economic evaluations. Three studies also included direct non-healthcare costs such as travel costs to the healthcare facility [34,45,46]. Three studies additionally incorporated indirect non-healthcare costs such as productivity loss, lost wages, and income lost by family caregivers [36,47,48].…”
Section: Diseasementioning
confidence: 99%
“…telephone calls) by care managers/nurse specialists to monitor and improve antidepressant adherence [37,46,57] • Pocket reminder cards for practice teams to enable patient assessment, education and activation of treatment [46] Heart failure • Standardized detailed educational program received at discharge with information on low-salt diet, self-monitoring of blood pressure and symptoms, daily weight, smoking cessation, etc. [32,49] • Nurse led program with home visit and regular telephonic follow-up to stress treatment adherence [45] • Telemanagement system stimulating patients to daily call in and answer a short health questionnaire. Information was stored and automatically analyzed by decision support tools [33,60] • Pharmacists studied guidelines, key concepts in pharmaceutical care [58] • Teaching patients better self-management skills by instructing and encouraging them to monitor their health [49] • Home visits by specialist nurse from HF clinic who provided hospital care, followed by short consultation nurse and physician after each visit [59] • Alerts were set in telemanagement system for abnormalities requiring immediate intervention by nurse [33] • Icons used for medication containers matching with icons on written instruction about medication [58] • Cardiologists were care managers and documented treatment plan [32] • General education about disease and treatment, individualized physical training program, recognizing early triggers of exacerbation, importance of smoking cessation [61,62] • Multidisciplinary care team plus home visits by nurse providing hospital care at home [43] • Pulse oximeter with modem system which is able to transmit information on arterial oxygen saturation through telephone line to a receiving station where tele-assistance nurse is available for tele-consultation [34] • NA…”
Section: Diseasementioning
confidence: 99%
“…Whether a DMP is a cost-effective way to manage these patients is not well established. The studies suggest a DMP may be cost effective or the extra cost associated with a DMP is acceptable (131,(139)(140)(141)(142). In a recent analysis by Whellan et al (143), an interesting concept based on the American system of reimbursement is presented.…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 99%
“…Importantly, even programs with a net positive impact on direct costs will likely prove to be substantially cost-effective, given the achievable improvements in HF-related morbidity and mortality. Within a randomized, controlled investigation of a 12-month nursetelephone intervention 26 with an average interventional cost of $2177 per patient, Herbert et al 27 observed an incremental overall societal cost (including such costs as telephone and transportation) ranging between $15 000 and $18 000 per quality-adjusted life year (QALY) gained. From the more usual perspective of payer cost, the incremental cost per QALY was between $3100 and $3700.…”
Section: Benefits On Healthcare Cost and Cost-effectivenessmentioning
confidence: 99%